The role of expertise in Public Policy of Equality in Spain - Calvo Borobia, Kerman; Gutierrez Sastre, Marta; Mena Martínez, Luis; Murillo de la Vega, Soledad (Investigaciones Feministas (Feminist Research), 2015)
This article discusses expert knowledge on gender equality in Spain. The analysis, in the first place, explains State intervention on gender equality in Spain from a historical perspective with a specific focus on the role of expert knowledge in this process; in the second place, the paper traces differences in expert narratives in relation to the meaning of equality; lastly, it assesses the influence of expert communities on shaping power configurations, with a comprehensive definition of impact that goes beyond the discussion of women’s issues. The article draws on qualitative methodologies (interviews and focus groups) to portray the views of expert women both in Academia and in the private sector; theoretically, a typology of expert knowledge is defended together with a discussion of the conflictive ways in which these types intersect with one another.
Keywords: Expert knowledge; Public Policies; Mainstreaming; Expert women.